0-Connectedness in Topological Spaces (International Journal of Scientific Research and Management (IJSRM), 2017)
In this paper, we introduce a new form of connectedness in topological space called b0-connectedness which is stronger form of b-connectedness and weaker form of connectedness. We also investigate some special properties of b0-connectedness. We further consider the components of b0-connectedness